All polarization-maintaining assively mode-locked yb-doped fiber laser : pulse compression using an anomalous polarization-maintaining photonic crystal fiber - Cuadrado-Laborde, Christian (2019)
Fil: Cuadrado-Laborde, Christian. Universidad de Valencia. Facultad de Física. Departamento de Física Aplicada; España